International Protection in Context of Property - ODOK, Joseph Abang; NABIEBU , Miebaka (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2024)
This work explores the international legal framework for the protection of property rights, focusing on the intersection of state sovereignty and individual ownership. It delves into the concept of 'eminent domain,' which grants states the authority to acquire private property for public purposes, often justified by the legal maxim salus populi est suprema lex (the welfare of the people is the supreme law). Despite legal provisions mandating compensation, outdated valuation methods and ineffective implementation of resettlement and rehabilitation schemes have left many property owners vulnerable and inadequately compensated. The study also highlights the international legal protections for property rights as enshrined in various international instruments, including the Universal Declaration of Human Rights (UDHR) 1948 and the European Convention on Human Rights (ECHR) 1950. Additionally, it examines the guidelines issued by the Economic Commission for Europe (1996), international investment law, and other covenants such as the International Covenant on Civil and Political Rights (ICCPR) 1966, all of which seek to safeguard property rights against arbitrary state actions. A comparative analysis of property rights protection across different jurisdictions, such as the United States and the United Kingdom, is conducted to illustrate the diverse approaches adopted by states. The role of international bodies and conventions, such as the Rio Declaration (1992), Convention on Biological Diversity, and the Vienna Declaration (1993), in protecting the property rights of marginalized and indigenous peoples is also examined. The study concludes by exploring landmark cases like Beyeler v. Italy (1997) and Sandu and Others v. The Republic of Moldova and Russia, where international courts have addressed issues related to the expropriation and protection of property rights. It argues that while international legal frameworks provide significant protection, gaps remain, particularly in addressing issues related to fair compensation, the protection of indigenous lands, and the interplay between property rights and environmental sustainability.